A Study of Atmospheric Aerosols in The Bahamas Using Camera Lidar and Star Photometry Techniques - Kabir, Amin S.; Sharma, Nimmi C.; Knowles, Edward; Gagnon, Seth; Fagnoni, Justin; Barnes, John E. (International Journal of Bahamian Studies, 2023)
Aerosols, the tiny suspended particles in the atmosphere, are a widely studied topic around the world due to their effects on the Earth’s radiation budget, climate change, and human health. Knowledge of the spatial and temporal distribution of aerosols is essential to assess air pollution and predict potential climate change. This study measured aerosol optical depth (AOD) and altitude-dependent aerosol extinctions in Nassau, The Bahamas simultaneously using a camera-based imaging lidar (CLidar). The bistatic geometry of the setup which consisted of a wide-angle lens fitted to a charge-coupled device (CCD) camera, allowed for the measurement of extinctions at all altitudes at once without requiring expensive timing electronics common to lidars. A case study was conducted on November 5, 2018. The top of the boundary layer beyond which aerosol extinction was nearly zero was detected at ~ three km above sea level. Due to the excellent resolution of the CLidar at lower altitudes, variations of aerosol concentrations within the boundary layer are efficiently detected. Optical depth was measured using the same CLidar camera at the same time, utilising star photometry, and was found to be 0.043 ± 0.040. The value falls within the range of assumed values of AOD near the regions obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua satellite.